Efficiency in the reduction of chromium by a wild bacterium in a Batch treatment type using residual water substrate from the municipality of Pasto, Colombia - Guerrero Ceballos, Deisy Lorena; Pinta Melo, Jhonatan; Fernandez Izquierdo, Pablo; Ibarguen Mondragón, Eduardo; Hidalgo Bonilla, Sandra Patricia; Burbano Rosero, Edith Mariela (Universidad y Salud, 2017)
Objective: To evaluate the efficiency in the reduction of chromium in a Batch treatment type, using municipal residual water substrate inoculated with a wild bacterium. Materials and methods: The reduction percentage of hexavalent chromium of three wild bacteria previously isolated from residual water from the Pasto River was verified at laboratory scale (Bacillus thuringiensis, Bacillus amyloliquefaciens and Paenibacillus sp.); the isolated that showed the highest percentage of reduction of Cr was selected and was subjected to different treatments. The analysis of results was done using descriptive statistics. Results: B. thuringiensis, B. amyloliquefaciens, and Paenibacillus sp., presented percentages of reduction of Cr (VI) of 82,01%; 80,85% and 79,27%, respectively. It was determined that the third treatment (nonsterile water from the Pasto River with B. thuringiensis) presented significant differences with regard to the other (p = 0.0001 α = 0.05), concluding that B. thuringiensis reduces in greater proportion the Cr (VI). The results found in this research are promising in the field of bioremediation of contaminated effluents with Chrome since they may be taken as the basis for implementing strategies of bioremediation on a large scale. Conclusion: The bacteria B. thuringiensis presented high efficiency in the reduction of hexavalent chromium (99.42%) when implemented in a treatment at laboratory scale of residual nonsterile water.